The effects of half-time re-warm-up protocols on speed, agility, and power in recreational futsal athletes / Muhammad Irham Hakimi Hussain ... [et al.]. - Hussain, Muhammad Irham Hakimi; Mohamed, Muhamad Noor; Md Radzi, Noor Azila Azreen; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Shari, Maisarah; Raja Hussain, Raja Nurul Jannat (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Re-warm-up (RWP) strategies during half-time breaks may sustain athletic performance and reduce injury risk [1,2]. This study investigates a three-minute RWP program’s effect on futsal players’ fitness performance (speed, agility, power) and compares RW with no RWP. Despite warm-up benefits, inactivity during breaks diminishes performance, underscoring RW importance [3]. Sixteen recreational male youth futsal players were recruited based on training and competition criteria. A three-minute re-warm-up (RWP) which involved running, skipping, jumping, and sprinting drills were conducted during half time break. Fitness metrics including speed (20m sprint), agility (T-test), and power (broad jump) were measured pre- and post-intervention. Comparisons were made between RW and control conditions (fully rest).